Implementation of Strategic Management in the Tahfidz Program at Madrasa - Wati, Ida; Yetri, Yetri; Thahir, Andi; Dewi, Asmara (Journal of Advanced Islamic Educational Management, 2024)
The study aims to determine and analyse the implementation of strategic management in the tahfidz program at MTs N 2 Bandar Lampung. The type of research used is descriptive qualitative. The data collection methods used were interview, observation, and documentation. The collected data were analysed through data reduction procedures, data presentation and conclusion drawing. Data validity test was conducted by triangulation. The results of the study found that: 1) The formulation of the strategy for developing the Qur'an tahfizh program, namely the vision of realising religious people and the mission of developing the potential of students according to their interests and talents and increasing the competence of students through intensive coaching both academic and non-academic. The goal is to produce students who have the character of memorising the Qur'an, facilitate students in learning to memorise the Qur'an and equip students with the knowledge of Tahfidz Al-Qur'an as capital for further schooling. The strengths are the teaching staff or mentors, quite a lot of enthusiasts, full support from the madrasa head. The weaknesses are the ups and downs of student enthusiasm and motivation, the absence of dormitories. The opportunities are support from parents, career paths for students for further schooling, and a better image of the institution. 2) Implementation of the development strategy of the fullday Al-Qur'an tahfidz class program, namely the fullday Al-Qur'an tahfidz class program that has been formulated and implemented including the targets to be achieved. Routine activities on Monday-Thursday at 14.00-16.00. Memorisation and muroja'ah, sima'an, memorisation test, certificate collection and tabarukan. The fullday Qur'an Tahfidz class is headed by Aisyah. There is no difference between the culture or habits carried out by regular students and Tahfidz Al-Qur'an students. the leadership style in the Tahfidz Al-Qur'an program is an analytical leader. 3) Evaluation of the development strategy of the Tahfidz Al-Qur'an program is a review carried out directly and also periodically, namely meetings every 2 months. Tahfidz with the most enthusiasts at MTs N 2 Bandar Lampung.